Ground‐penetrating radar (GPR) investigations of a large‐scale buried ice‐marginal landsystem, Skeiðarársandur, SE Iceland. (20th March 2022) - Harrison, Devin; Ross, Neil; Russell, Andrew J.; Jones, Stuart J.
Abstract : The sedimentary record of Icelandic ice‐contact environments provides critical insights into past glacier margin dynamics and position, relative sea level, and the geomorphic processes that drive the evolution of proglacial environments. This important archive has been little exploited, however, with most glacier and sea‐level reconstructions based on limited sedimentary exposures, coring and surface geomorphic evidence. We report an extensive (42 km of data within a 24‐km 2 study area) and deep (reflections recorded at depths up to 100 m) low‐frequency (40 and 100 MHz) ground‐penetrating radar (GPR) survey of the Sandgígur moraines, SE Iceland. GPR profiles reveal a much larger (67 m high) and extensive (1.25 km wide) buried moraine ridge than that suggested by surface topography (typically 125 m wide and 7 m high). These data reveal that the Sandgígur moraines was deposited during a major Holocene re‐advance of Skeiðarárjökull. The moraine ridge is buried by sediments dominated by glacifluvial deposits with an estimated sediment volume of 1.04 km 3 . We combine GPR‐derived subsurface architecture and the surface morphology to develop a conceptual model detailing the geomorphic evolution of the moraine and surrounding region. These results provide new insights into the Holocene evolution of Skeiðarársandur, identifying the presence of a former major ice‐margin position, as well as a past relative sea‐level limit. Furthermore, we establish that sediment supply and available terrestrial accommodation space are dominant drivers in the formation and evolution of vast sandar environments.